Redactable blockchain supporting trapdoor revocation and limited number of redactions - Yue CHEN; Zenghang HAO; Jianghong WEI; Xuexian HU; Dongmei YANG (Tongxin xuebao)
Aiming at the problem that although the existing redactable blockchain schemes that support trapdoor revocation could revoke the redaction permissions of trapdoor holders, but they were unable to limit the number of redactions using trapdoors, indicating an issue where the management of editing permissions was not adequately refined, a revocable chameleon hash with limited number of redactions was proposed, based on which a new redactable blockchain scheme was proposed.Specifically, the proposed scheme included a master trapdoor, a subordinate trapdoor, and the generated witness.The subordinate trapdoor was deployed for data modification, while the master trapdoor was employed to revoke the subordinate trapdoor, thus accomplishing the objective of revoking editing permissions.Meanwhile, the witness was developed to strictly limit the number of edits via the subordinate trapdoor to one time.The proposed scheme is proved to be secure under the standard complexity assumptions.Theoretical analysis and simulation experiments indicate that the proposed scheme has advantages in terms of security guarantee, when compared with the existing schemes supporting trapdoor revocation.At the same time it introduces little additional computation overhead, and thus has certain practicality.